Peran BMT BMT Binamas Kutoarjo Terhadap Pemberdayaan UMKM Melalui Pembiayaan Murabahah - Achmad Afifudin; M. Nurul Fahmi; Miftahur Rahman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research is a qualitatife descriptive study that aims to determine the role of BMT Bina Ummat Sejahtera through murabahah financing in an effort to strengthen the economy of MSMEs. Data collection techniques use observation, interviews, and documentation. From the results of the study it was conclude that The role given by BMT was seen from capital and guidance. Capital plays a role in strengthening the economy of MSMEs, while the guidance given by BMT to members is not maximal because it is only seen from the monthly installments of members. Murabahah financing plays a role in strengthening the economy of MSMEs seen from the development of businesses characterized by the amount of income, profits, and labor. Also seen from welfare which is marked by the fulfillment of basic, additional, and educational needs.